The Study on Dorsal Venous Arch of Upper Limb Among Nepalese Medical Students at Tertiary Level Teaching Institute - Tiwari, Nripendra; Budhathoki, Deepesh; Malla, Krishna Banshi (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: Dorsal venous arch of upper limb is the beginning site for cephalic and basilic veins. The superficial veins are clinically important for venipuncture, blood collection and blood donation as well as for health screening and testing, intravenous transfusion for the emergency treatment of hypovolemic shock. Veins of the upper limb are also used for total parental nutrition, therapeutic invasive procedure and blood samples. The Dorsal Venous Arch is superficially placed and can be easily made prominent by putting a tourniquet at the wrist for any such surgical and therapeutic purposes. Methods: It was a cross-sectional observational study conducted in 200 hands among 100 individuals from MBBS first and second year students studying at a Medical College. Body Mass Index (BMI) of individuals was calculated to observe the correlation between length of the dorsal venous arch and BMI. Results: The mean±s.d. length of dorsal venous arch in male on right hand (20.7±2.4 cm) was significantly greater than in female on right hand (19.4±2.1 cm).There was no significant difference in length of dorsal venous arch on left side between male (20.1±2.2 cm.) and female (19.3±1.8 cm). Conclusions: The length of the dorsal venous arch on right hand was found significantly greater in male than in female. Also the length of dorsal venous arch on right side was found to be more than on left side in both sexes. The male students are significantly older, heavier and taller than females.